P-modified biochar alters the microbial community in heavy metal-contaminated soils by regulating nutrient supply balance - Qiang Wang; Chenyang Xu; Kai Pan; Xiaogang Wu; Yanshuo Pan; Chengjiao Duan; Zengchao Geng (Biochar)
Abstract Phosphorus (P)-modified biochar demonstrates dual capabilities for heavy metal immobilization and soil quality enhancement. However, the underlying mechanism of microbial response to changes in soil properties is still unclear. In this study, P-modified biochar, prepared by co-pyrolysis of apple tree branches with K3PO4, was used for removal of heavy metals from the soils near a mining area. Effects of P-modified biochar on the microbial communities in soil were investigated and the key driving factors were identified. Adding P-modified biochar reduced the bioavailable cadmium and lead contents of the soil by 28.21% and 28.64%, respectively, mainly through improved co-precipitation and cation exchange. In turn, the cadmium and lead concentrations in maize grains were reduced by 36.52% and 61.82% respectively. Meanwhile, the richness and diversity of soil bacteria significantly decreased with the addition of P-modified biochar (P < 0.05). Microbial multi-trophic ecological network module analysis and partial least squares pathway modeling indicated that biochar changed the capacity of the soil to provide microorganisms with nitrogen and P, requiring the key microbial taxa (modules 1 and 3) to adjust. Modules 1 and 3 played important but opposite functions in the nitrogen and P cycle of the soil. This further led to variations in the composition and structure of microbial communities in soil. Particularly, changes in the bioavailability of heavy metals showed a negligible effect on soil microbial communities. This study emphasizes that P-modified biochar can efficiently reduce soil heavy metal bioavailability and alter the microbial community by regulating nutrient supply balance. Graphical Abstract